2014
DOI: 10.2147/ndt.s65721
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, persistence, and medication discontinuation in patients with attention-deficit/hyperactivity disorder – a systematic literature review

Abstract: Untreated attention-deficit/hyperactivity disorder (ADHD) can lead to substantial adverse social, economic, and emotional outcomes for patients. The effectiveness of current pharmacologic treatments is often reduced, due to low treatment adherence and medication discontinuation. This current systematic literature review analyzes the current state of knowledge surrounding ADHD medication discontinuation, focusing on: 1) the extent of patient persistence; 2) adherence; and 3) the underlying reasons for patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 80 publications
4
102
0
Order By: Relevance
“…Under these real-world conditions, ~70% of patients completed the 1-year study phase without discontinuing pharmacological treatment: 128 patients continued to receive MPH, 25 had switched to dextroamphetamine, and 10 had switched to atomoxetine. In line with randomized, controlled clinical trials, AEs and lack of efficacy were reported as the most common reasons for treatment discontinuation 59,60. Moreover, the study revealed that approximately half of the patients preferred immediate-release MPH over extended-release formulations, highlighting the need for clinicians to consider alternative MPH formulations on an individual patient basis.…”
Section: Dose Optimization In Clinical Trials and Naturalistic Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…Under these real-world conditions, ~70% of patients completed the 1-year study phase without discontinuing pharmacological treatment: 128 patients continued to receive MPH, 25 had switched to dextroamphetamine, and 10 had switched to atomoxetine. In line with randomized, controlled clinical trials, AEs and lack of efficacy were reported as the most common reasons for treatment discontinuation 59,60. Moreover, the study revealed that approximately half of the patients preferred immediate-release MPH over extended-release formulations, highlighting the need for clinicians to consider alternative MPH formulations on an individual patient basis.…”
Section: Dose Optimization In Clinical Trials and Naturalistic Studiessupporting
confidence: 52%
“…Buitelaar et al evaluated the long-term efficacy and tolerance of OROS-MPH, wherein no evidence of withdrawal or rebound was reported after treatment discontinuation 64. As previously reported in randomized controlled trials, the most common reason reported for treatment discontinuation was AE 60. Ginsberg et al reported a lower rate (2.3%) of AE-induced discontinuation during the extension phase of the MPH-LA study compared with other open-label extension studies such as OROS-MPH (18.5%) 55,63.…”
Section: Dose Optimization In Clinical Trials and Naturalistic Studiesmentioning
confidence: 97%
“…Attention-deficit/hyperactivity disorder (ADHD) is the most common childhood disorder in psychiatric outpatient clinics, and it affects approximately 5.3% of the school aged population 1. ADHD has been regarded as a chronic condition that may continue through adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, children in the PG may have performed more poorly than those in the CG because they were not adherent to their stimulant treatment regimens, a possibility consistent with recent literature on medical treatment of children and adults with ADHD. 41 Follow-up intervals were linked to children's ages and dates of enrollment into P219C, not to medication start and stop dates, and there was wide variability in treatment duration, with some participants continuing their first prescription for as little as one month. Such variability limits the interpretation of study findings.…”
Section: Discussionmentioning
confidence: 99%